2005
DOI: 10.1021/es049110m
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Volatile Organic Compounds over a Semiconductor Industrial Park in Taiwan

Abstract: This study examined volatile organic compounds (VOC) concentration in ambient air collected during the years 2000--2003 at several different locations of Hsinchu Science-based Industrial Park (HSIP) in Taiwan. A canister automated GC-MS system analyzed the volatile organics in ambient air grasp samples according to T0-15 method. Oxygenated volatiles were the most abundant VOC detected in HSIP followed by aromatics that are commonly used as solvents in the semiconductor industries. The major components measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
(34 reference statements)
2
19
4
Order By: Relevance
“…Statistically significant differences (mean ± 1σ) between the concentrations during day and night time periods are noticeable in the cases of benzene (7.4 ± 14.8 µg m -3 and 17.0 ± 25.4 µg m -3 ), toluene (8.5 ± 15.8 µg m -3 and 22.8 ± 32.6 µg m -3 ), xylenes (2.5 ± 4.6 µg m -3 and 7.8 ± 13.4 µg m -3 ) and TRS (2.1 ± 1.3 µg m -3 and 3.3 ± 1.9 µg m -3 ). Thus, the concentrations of these pollutants were higher during the night than during the daytime period, which is in accordance with the results of measurements in the ambient air of the Kaohsiung Petroleum Refinery in Taiwan (Chiu et al, 2005a;Chiu et al, 2005b). These pollutants were emitted from low altitude sources located at the oil refinery and petrochemical industry.…”
Section: Daily Variation Of the Ambient Air Concentrationsupporting
confidence: 88%
See 1 more Smart Citation
“…Statistically significant differences (mean ± 1σ) between the concentrations during day and night time periods are noticeable in the cases of benzene (7.4 ± 14.8 µg m -3 and 17.0 ± 25.4 µg m -3 ), toluene (8.5 ± 15.8 µg m -3 and 22.8 ± 32.6 µg m -3 ), xylenes (2.5 ± 4.6 µg m -3 and 7.8 ± 13.4 µg m -3 ) and TRS (2.1 ± 1.3 µg m -3 and 3.3 ± 1.9 µg m -3 ). Thus, the concentrations of these pollutants were higher during the night than during the daytime period, which is in accordance with the results of measurements in the ambient air of the Kaohsiung Petroleum Refinery in Taiwan (Chiu et al, 2005a;Chiu et al, 2005b). These pollutants were emitted from low altitude sources located at the oil refinery and petrochemical industry.…”
Section: Daily Variation Of the Ambient Air Concentrationsupporting
confidence: 88%
“…Statistically significant differences between the concentrations during day and night time periods are noticeable in the cases of toluene too; 11.6 ± 14.5 µgm -3 and 22.8 ± 29.2 µgm -3 at Vatrogasni dom receptor, and 8.5 ± 15.8 µgm -3 and 22.8 ± 32.6 µgm -3 at Vojlovica, xylenes; 2.5 ± 4.6 µgm -3 and 7.8 ± 13.4 µgm -3 as well as total reduced sulphur (TRS); 2.1 ± 1.3 µgm -3 and 3.3 ± 1.9 µgm -3 at Vojlovica receptor respectively. The mean concentrations of NH 3 were higher during the daytime (12.3 ± 31.3 µgm -3 ) than those during the night period (7.5 ± 11.6 µgm -3 ) at Vatrogasni dom receptor, while the mean of daily concentrations of NO 2 during the daytime (12.9 ± 14.8 µgm -3 ) were statistically significantly lower than those during the night (20.1 ± 11.5 µgm -3 ) at Vatrogasni dom receptor, unlike the daily variations of the concentrations measured in the ambient air of the Kaohsiung Petroleum Refinery in Taiwan (Chiu et al, 2005a;Chiu et al, 2005b). The results showed that the concentrations of pollutants originating from low altitude emission sources like organic pollutants were higher twice and more at night.…”
Section: Daily Variation Of the Ambient Air Concentrationmentioning
confidence: 74%
“…These aforementioned results and discussions supported the existence of temporary dynamic changes in the indoor and the outdoor chemical concentrations, which are highly dependent on whether the chemical was emitted from the indoor manufacturing process during the observation period and the wind speed in the outdoor environment (Tsai et al, 2004;Chiu et al, 2005). The chemicals that accumulate around the outdoor environment of a manufacturing facility may be drawn into the facility again and consequently deteriorate the indoor environment (Li et al, 2009).…”
Section: Indoor/outdoor Concentration Ratio For the Identification Ofmentioning
confidence: 87%
“…The eight compounds of the ethanol, acetone, and PGMEA, 2-propanol, 1,2,3-trimethylbenzene, 1,3,5-trimethylbenzene, ethyl acetate, and 1,2,4-trimethylbenzene have been confirmed as the raw materials used in manufacturing processes after examining the safety data sheets (SDSs) of these areas. In addition, the five compounds of the o-xylene, p-pylene, m-xylene, toluene, and MTBE could be associated with traffic emissions (NIOSH, 1996;Chiu et al, 2005;Hsieh et al, 2006). The two compounds of the toluene and phenol have been identified as the byproducts associated with the thermal decomposition of the photoresist (OEHHA Toxicity Criteria Database, 2015).…”
Section: Concentrations Of Each Individual Voc (C Voci ) In Thementioning
confidence: 99%